2019
DOI: 10.1073/pnas.1908771116
|View full text |Cite
|
Sign up to set email alerts
|

Adaptational lag to temperature in valley oak ( Quercus lobata ) can be mitigated by genome-informed assisted gene flow

Abstract: SignificanceForested ecosystems provide many ecological, economic, and societal benefits, but those benefits are threatened by climate change. Conservation strategies often assume that plants are currently growing in conditions well-suited to their growth, survival, and reproduction, regardless of whether this assumption is valid. We show that an ecosystem-foundational species in California, valley oak (Quercus lobata), is already mismatched to current temperature and will likely experience further declines in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
133
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(139 citation statements)
references
References 47 publications
1
133
1
4
Order By: Relevance
“…Here, the concept of “genomic vulnerability” is defined as the mismatch between current and predicted future genomic variation, where the vulnerability of individual populations is a measure of the amount of genomic change required to track climate change over time (Dawson, Jackson, House, Prentice, & Mace, 2011). This information can be used to profile population vulnerability over species distributions, helping to identify populations most at risk from climate change, and reveal “climate‐ready” genotypes that can be used to enhance climate resilience in restoration plantings (Breed et al., 2019; Broadhurst et al., 2008; Browne, Wright, Fitz‐Gibbon, Gugger, & Sork, 2019; Prober et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Here, the concept of “genomic vulnerability” is defined as the mismatch between current and predicted future genomic variation, where the vulnerability of individual populations is a measure of the amount of genomic change required to track climate change over time (Dawson, Jackson, House, Prentice, & Mace, 2011). This information can be used to profile population vulnerability over species distributions, helping to identify populations most at risk from climate change, and reveal “climate‐ready” genotypes that can be used to enhance climate resilience in restoration plantings (Breed et al., 2019; Broadhurst et al., 2008; Browne, Wright, Fitz‐Gibbon, Gugger, & Sork, 2019; Prober et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying genomic patterns associated with adaptation in wild populations can provide information to support management strategies as well as facilitate fundamental discoveries (Garner et al, 2016;Sgrò, Lowe, & Hoffmann, 2011). We can improve our understanding of the response of species to changing climates and their evolutionary potential by leveraging knowledge about adaptive genetic variation in natural populations (Browne, Wright, Fitz-Gibbon, Gugger, & Sork, 2019;Razgour et al, 2019;Sork, 2017). Genotype-environment association (GEA) methods are used to identify potentially adaptive loci in non-model systems based on correlations between allele frequencies and environmental data.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are now substantial genomic resources available, including an annotated reference genome (Sork, Fitz-Gibbon, et al, 2016) and transcriptome (Cokus et al, 2015). In addition, surveys of trait variation in the field (e.g., Albarrán-Lara et al, 2015) and ongoing research at a large-scale common garden that includes samples at multiple spatial scales (Delfino Mix et al, 2015) suggests variation in fitness as measured by leaf and growth-related traits consistent with local adaptation to current or past environmental gradients (Browne et al, 2019). Furthermore, Browne et al (2019) demonstrated that SNPs can be used to identify genotypes associated with higher growth rates under warmer temperatures in this species.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, surveys of trait variation in the field (e.g., Albarrán-Lara et al, 2015) and ongoing research at a large-scale common garden that includes samples at multiple spatial scales (Delfino Mix et al, 2015) suggests variation in fitness as measured by leaf and growth-related traits consistent with local adaptation to current or past environmental gradients (Browne et al, 2019). Furthermore, Browne et al (2019) demonstrated that SNPs can be used to identify genotypes associated with higher growth rates under warmer temperatures in this species. Previous landscape genomic studies in Q. lobata were limited in sample size or the number of genetic loci (Sork, Squire, et al, 2016), necessitating further study, but provide some candidates for comparison along with those from a water stress gene expression experiment (Gugger et al, 2017).…”
Section: Introductionmentioning
confidence: 99%